Roti Bengali: milk belongs to the cow, but the bull cow gets the name / Nazima Versay Kudus - Versay Kudus, Nazima (Academy of Language Studies, 2023)
Penang is eminent for its food - nasi kandar, asam laksa, pasembur to name a few. One famous dish is its old-fashioned bread, Roti Bengali. It is said that the bread is given such a name due to the turban-like shape of the bread which looks like the head covering worn by the Bengalis. Of course this is a misnomer and can be an offense to the Sikhs. It is the Sikhs who wear the turban or the dastar not the Bengalis. In the past, in Penang, fresh daily bread like Roti Bengali were delivered to homes by the Mamak Roti on bicycles, later on motorbikes. The presence of the Mamak Roti is easily identifiable with its iconic bike bell sound from afar. Upon hearing the sound, children and mothers would wait at the front gate welcoming the Mamak Roti just like the homecoming of a family member. Mothers would purchase the freshly baked bread as a staple while children would choose snacks such as Chickadees, Twistees, Haw Flakes and Keropok Popo. The Mamak offered interest-free loans - any purchase of the day would go into one of the popular items of the 70s, the buku tiga lima or 555 notebook that kept tabs of debts, paid at the end of the month